2021
DOI: 10.18502/cmm.7.2.7157
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Candida prosthetic valve endocarditis and COVID-19 comorbidity: A rare case

Abstract: Background and Purpose: Coronavirus disease 2019 (COVID-19) and Candida prostatic valve endocarditis present various clinical manifestations which may overlap;hence, discrimination between them is extremely difficult. Case report: The case was a 66-year-old man with a past medical history of mitral and aortic valves replacement one year before COVID-19 co-infection. He was admitted with fever (for 7 days), shortness of breath, cough, seizure, lethargy,headache, and 85% oxygen saturation. Transesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…9 A study in 2021 suggested that the SARS-CoV-2 virus pandemic has outlined a new problem for the diagnosis of cardiovascular diseases and further care and treatment. 4 A review of endocarditis after COVID-19 showed that the highest percentage of infective endocarditis was related to the mitral valve (33%) of the heart, 8 which is similar to our finding. Patients, who do not have surgery on an infected valve, pose a 100% risk of mortality while in patients who undergo cardiac valve replacement, 45% is reported.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…9 A study in 2021 suggested that the SARS-CoV-2 virus pandemic has outlined a new problem for the diagnosis of cardiovascular diseases and further care and treatment. 4 A review of endocarditis after COVID-19 showed that the highest percentage of infective endocarditis was related to the mitral valve (33%) of the heart, 8 which is similar to our finding. Patients, who do not have surgery on an infected valve, pose a 100% risk of mortality while in patients who undergo cardiac valve replacement, 45% is reported.…”
Section: Discussionsupporting
confidence: 89%
“…Over the past year, with the increasing number of patients with COVID‐19, cases of COVID‐19 patients presenting with infective endocarditis have increased 9 . A study in 2021 suggested that the SARS‐CoV‐2 virus pandemic has outlined a new problem for the diagnosis of cardiovascular diseases and further care and treatment 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a case of endocarditis caused by C . tropicalis was reported in an Iranian patient with prosthetic heart valves, who died despite receiving liposomal amphotericin B [ 20 ]. Another case of endocarditis caused by C .…”
Section: Discussionmentioning
confidence: 99%